Unicondylar knee arthroplasty using cobalt-chromium implants in patients with self-reported cutaneous metal hypersensitivity. (February 2019) - Walker, T.; Rutkowski, L.; Innmann, M.; Panzram, B.; Herre, J.; Gotterbarm, T.; Aldinger, P. R.; Merle, C.
Abstract : Aims: The treatment of patients with allergies to metal in total joint arthroplasty is an ongoing debate. Possibilities include the use of hypoallergenic prostheses, as well as the use of standard cobalt-chromium (CoCr) alloy. This non-designer study was performed to evaluate the clinical outcome and survival rates of unicondylar knee arthroplasty (UKA) using a standard CoCr alloy in patients reporting signs of a hypersensitivity to metal. Patients and Methods: A consecutive series of patients suitable for UKA were screened for symptoms of metal hypersensitivity by use of a questionnaire. A total of 82 patients out of 1737 patients suitable for medial UKA reporting cutaneous metal hypersensitivity to cobalt, chromium, or nickel were included into this study and prospectively evaluated to determine the functional outcome, possible signs of hypersensitivity, and short-term survivorship at a minimum follow-up of 1.5 years. Results: At a mean follow-up of three years (1.5 to 5.7), no local or systemic symptoms of hypersensitivity to metal were observed. One patient underwent revision surgery to a bicondylar prosthesis due to a tibial periprosthetic fracture resulting in a survival rate of 98.8% (95% confidence interval (CI) 91.7 to 99.8; number at risk, 28) at three years with the endpoint of revision for any reason and a survival rate of 97.6% (95% CI 90.6 to 99.3; number at risk, 29) for the endpoint of all reoperations. Clinical outcome was good to excellent with a mean Oxford Knee Score of 42.5 (sd 2.5; 37 to 48). Conclusion: This study is the first demonstrating clinical results and survival analysis of UKA using a CoCr alloy in patients with a history of metal hypersensitivity. Functional outcome and survivorship are on a high-level equivalent to those reported for UKA in patients without a history of metal hypersensitivity. No serious local or systemic symptoms of metal hypersensitivity could be detected, and no revision surgery was performed due to an adverse reaction to metal ions.